FORMULASI PEDOMAN PERANCANGAN PERPUSTAKAAN ANAK DENGAN KONSEP RAMAH ANAK: FORMULASI PEDOMAN PERANCANGAN PERPUSTAKAAN ANAK DENGAN KONSEP RAMAH ANAK - Indira Jihan Shafira; Purnama Salura; Indri Astrina Wirakusumah (Universitas Telkom, 2026)
Abstract : The limited number of children’s libraries in Indonesia contributes to low literacy levels among. This condition is further exacerbated by the lack of libraries designed using a child friendly architectural approach. Therefore, design guidelines are needed to translate children’s needs and characteristics into library environments that support their growth and development. This study aims to formulate design guidelines for children’s libraries based on child-friendly concepts. A qualitative descriptive method was employed through literature review and precedent studies. The theoretical framework includes child-friendly concepts, children’s library services and activities, and the theories of architectural anatomy and property composition. The precedent studies were conducted on the CALS Children’s Library in the United States and the Shirasagi Children’s Library in Japan. The study identifies three main architectural aspects, namely quality of child-friendly spatial properties, inclusive child accessibility, and integrated spatial organization, as the basis for formulating design guidelines. These aspects support the creation of safe, comfortable, inclusive, and child-friendly library environments. The findings are expected to enrich the discourse on child-friendly architecture and serve as a reference for architects, library managers, and policymakers in developing educational spaces for children aged 10–12 years while supporting their needs, rights, learning experiences, and overall development. Keywords : Design Guidelines, Child-Friendly Concept, Children's Library.